2006
DOI: 10.1002/gps.1607
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to hospitalization in elderly manic patients with early and late‐onset bipolar disorder

Abstract: Relapse and rehospitalization were common among elderly manic patients with early-onset and late-onset bipolar disorder. Strategies which improve medication adherence are needed to help prevent recurring hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…With regard to our second hypothesis about differences between EOB and LOB, there were no statistically significant differences in treatment. This suggests that differences in symptomatology and etiology between older EOB and LOB patients reported by others (Lehmann and Rabins, ; Sajatovic et al ., ; Sajatovic et al ., ; Schouws et al ., ; Besga et al ., ; Shou‐Hung et al ., ) may be better reasons to distinguish between EOB and LOB. However, the older EOB patients may be a too heterogeneous group consisting of a mixed age of onset group with a very early, intermediate, and late age at onset (but all before the age of 50 years), with two cutoff points between the three groups, at 21 and 34 years (Geoffroy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to our second hypothesis about differences between EOB and LOB, there were no statistically significant differences in treatment. This suggests that differences in symptomatology and etiology between older EOB and LOB patients reported by others (Lehmann and Rabins, ; Sajatovic et al ., ; Sajatovic et al ., ; Schouws et al ., ; Besga et al ., ; Shou‐Hung et al ., ) may be better reasons to distinguish between EOB and LOB. However, the older EOB patients may be a too heterogeneous group consisting of a mixed age of onset group with a very early, intermediate, and late age at onset (but all before the age of 50 years), with two cutoff points between the three groups, at 21 and 34 years (Geoffroy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of the existence of subgroups with early, intermediate, and late age at onset (Geoffroy et al, 2013). Differences have been reported between older EOB and LOB patients concerning behavior prior to hospitalization and adherence with medication (Lehmann and Rabins, 2000), sex ratio (Sajatovic et al, 2005a), length of hospitalization (Sajatovic et al, 2005b;Oostervink et al, 2009), use of mood stabilizers, severity of illness and utilization of health services (Sajatovic et al, 2005b), cognitive impairment (Schouws et al, 2009), findings at neuroimaging (Tamashiro et al, 2008;Shou-Hung et al, 2011), and etiology of white matter hyperintensities (Besga et al, 2011;Gunde et al, 2011). On the other hand, other studies reported only few to no differences between older EOB and LOB patients, suggesting that distinguishing between late onset and early onset is of limited clinical relevance (Almeida and Fenner, 2002;Sajatovic et al, 2005a;Chu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies among patients with bipolar disorder have found a link between non-adherence to prescribed medication and hospitalization. An analysis of factors leading to hospitalization among elderly patients with bipolar mania found lack of adherence with prescribed psychiatric medication (for example, mood stabilizers) to be a major factor [ 14 ]. A study of adherence and outcomes among patients with bipolar disorder who were receiving antipsychotics, lithium, and antidepressants reported hospitalization rates of 73% for those classified as irregular medication users compared with 31% for regular users [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…While relatively rare in the community, high rates of geriatric bipolar disorder are seen in both inpatient and outpatient psychiatric treatment settings (3,4). Relapse and readmission is common among older patients with bipolar disorder, even among those individuals who have had the illness for many years (5). …”
Section: Introductionmentioning
confidence: 99%